Effect of Zn:Sn ratio and calcination temperature on phase transformation of Zn-Sn-O compound - Nakhanivej, Puritut; Tangcharoen, Thanit; Mekprasart, Wanichaya; Pecharapa, Wisanu (My University, 2016)
Zn-Sn-O powders were synthesized by simple co-precipitation method combined with calcination process using zinc chloride (ZnCl2) and tin (IV) chloride pentrahydrate (SnCl4·5H2O) as starting precursors of Zn and Sn in aqueous solution. The effect of precursors ratio on phase structure of Zn-Sn-O compound was investigated by varying ratio of Zn:Sn in the co-precipitation system. For the effect of calcination temperature, the as-precipitated product obtained at Zn: Sn ratio of 1:1 was calcined at different temperatures (400-900°C) to study phase transformation. Structural properties of as-precipitated and after-calcined powders were characterized by X-ray diffraction (XRD) while surface morphologies of final products were observed by scanning electron microscope (SEM), and thermogravimetric analysis (TGA) was used to study their thermal properties. The results indicate that the XRD pattern of Zn-Sn-O powders obtained at ratio of Zn greater than Sn can be assigned to mixed phase of ZnO and Zn2SnO4. On the other hand the XRD patterns of products obtained at ratio of Sn greater than Zn confirm a mixture of SnO2 and Zn2SnO4. For the effect of calcination temperature, the rarely spinel phase of Zn2SnO4 begin occur with mixed phase of ZnO and SnO2 at the calcination temperature of 600°C and pure spinel structure can be obtained at the temperature above 900°C.
Keywords: Phase transformation; Precursor ratio; Zn-Sn-O compound